2016
DOI: 10.1016/j.hrthm.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Purkinje fibers and arrhythmias; The GK Moe Award Lecture 2015

Abstract: Purkinje fibers/cells continue to be a focus of arrhythmologists. Here we review several new ideas that have emerged in the literature and fold them into important new points. These points include some proteins in Purkinje cells that are specific to Purkinjes, pacemaker function in Purkinje may be similar to that of the sinus node cell, sink-source concerns about tracts/sheets of Purkinje fibers, role of Ito in arrhythmias and genetic lesions in Purkinjes and their high impact on cardiac rhythm. Although new i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 38 publications
4
38
0
Order By: Relevance
“…Contemporary modalities are typically composed of point‐by‐point radiofrequency or cryotherapy ablation for ventricular arrhythmia ablation. Given the incredible redundancy and arborizing nature of Purkinje fibers,23 coupled with the trabeculated nature of the left ventricle, an approach using electroporation may be a promising alternative. Consistent with other noncardiac electroporation patterns of injury, the extent of injury found was not solely reliant on contact and confined to the tissue adjacent to the catheter tip, but a result of the electric field (V/cm) created 24, 25, 26, 27.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary modalities are typically composed of point‐by‐point radiofrequency or cryotherapy ablation for ventricular arrhythmia ablation. Given the incredible redundancy and arborizing nature of Purkinje fibers,23 coupled with the trabeculated nature of the left ventricle, an approach using electroporation may be a promising alternative. Consistent with other noncardiac electroporation patterns of injury, the extent of injury found was not solely reliant on contact and confined to the tissue adjacent to the catheter tip, but a result of the electric field (V/cm) created 24, 25, 26, 27.…”
Section: Discussionmentioning
confidence: 99%
“…1 Similarly, SKNA was recorded in 5.9% of the windows, whereas it was recorded more than 12.5% of time in a canine study. 17 This difference might be explained by the timing of recordings. In ambulatory animals, 14 we found that the stellate ganglion nerve activities were infrequently observed in the first few days after surgery but became very frequent one week later.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the endocardial pseudotendon of a normal rabbit ventricle (Figure 1A), a PC (Figure 1B), and a VM (Figure 1C). A PC was identified by its tapered cell morphology and a lack of transverse tubules 10. PCs and VMs were selected for patch studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, others showed that cardiac PCs and working myocytes share a common myogenic precursor and that migratory neuroectoderm‐derived populations do not contribute to the development of PCs 24, 25. While there is no consensus on the neuronal origin of the PCs, there is little doubt that the PCs are electrophysiologically different than the working VMs 10. Compared with VMs, the PCs have much smaller inward rectifier K+ current and much larger Ca 2+ ‐independent transient outward K + current 26.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation